ChemInform Abstract: Remote Oxidation of Aliphatic C—H Bonds in Nitrogen‐Containing Molecules. Issue 20 (April 2016) - Howell, Jennifer M.; Feng, Kaibo; Clark, Joseph R.; Trzepkowski, Louis J.; White, M. Christina
Abstract: A nitrogen complexation strategy using a strong Broensted acid (HBF4 ) or an azaphilic Lewis acid (BF3, not shown) enables remote, non‐directed C(sp 3 )—H oxidations of tertiary, secondary, and primary amine‐ and pyridine‐containing molecules with tunable iron catalysts.